La lingua italiana in una prospettiva di genere Atti del Seminario online promosso dagli Atenei di Firenze e Udine con il patrocinio dell'Accademia della Crusca (1° marzo 2022) - Monaco, Maria Paola (Proceedings e report, 2023)
It was 1987 when Alma Sabatini, following the request of the National Commission for Equality and equal Opportunities between women and men, established by the Presidency of the Council of Ministries, published The indications for a non-sexist use of the Italian language. Over thirty years after that publication, the topic has kept its relevance intact, becoming the keystone for reading and interpreting gender issues and policies. Starting from this context, the universities of Florence and Udine proposed a reflection on the relationship between gender and language, bringing the topic back to the center of the scientific debate, but free from media aspects which it often appears to be imbued with in public opinion and that, sometimes, end up undermining the true value of the relationship.